Food Influencers on Instagram: Followers’ Receptive Engagement through Verbal and Visual Intentional Dialogicity - Soto-Almela, Jorge; Suau-Jiménez, Francisca (Círculo de Lingüística Aplicada a la Comunicación, 2025)
Social media has become a cornerstone of influencer marketing for commercial promotion. When influencers create content describing a product, users engage in response—both verbally and visually, often through emojis—creating a polyphonic conversation that generally conveys positive emotions and judgments. This study examines the communication between Spanish-speaking gastronomic influencers and their followers by analysing a corpus of conversational threads from official Instagram accounts, adopting a pragmatic-discursive approach. Our goal is to offer a nuanced understanding of how intentional verbal and visual dialogicity shapes interactions, employing strategies aimed at promoting gastronomic content on social media. The findings hold social, professional, and discursive implications.
Keywords: interpersonal discourse; influencers; Instagram; emojis